2018
DOI: 10.1007/s11892-018-1031-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sex Differences in Adipose Tissue

Abstract: There is evidence related to the sex dichotomy in obesity in a variety of areas including adipocyte function, sex hormone effects, genetics, and metabolic inflammation leading to critical differences in adipose tissue biology. The sex and gender difference in adipose tissue is a factor that should be considered when studying an individuals' risk for obesity and metabolic dysfunction. This understanding is important for strategizing treatment and prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
162
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 136 publications
9
162
4
1
Order By: Relevance
“…Body fat distribution significantly differs between men and women [36][37][38]. Women have more SAT, whereas men have more abdominal VAT [16,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Body fat distribution significantly differs between men and women [36][37][38]. Women have more SAT, whereas men have more abdominal VAT [16,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have analyzed the effects of sex hormone levels on plasma lipid levels in children, and differences in HDL-C levels by sex during puberty have been related to the rise of testosterone levels in boys [ 51 ]. In addition, animal models have demonstrated that sex and sex hormones influence adipose tissue, gene expression profiles, regulating insulin resistance and lipolysis, as well as inflammatory tone and obesity [ 52 ]. Depending on sex, the level of specific sex hormones can improve or worsen metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on sex, the level of specific sex hormones can improve or worsen metabolic dysfunction. Estrogen generally provides a protective effect in females, while adequate androgen levels in males are important in promoting appropriate adiposity and metabolic status, and an increase of testosterone decreases abdominal obesity and the metabolic risk profile [ 52 ]. Indeed, a study that included healthy schoolchildren ranging from 12 to 15 years old showed that sex hormone-binding globulin levels were related to a decrease in HDL-C and apolipoprotein A-I levels during puberty in boys and to a decrease in TG levels during puberty in both sexes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, women had more SAT while men had more abdominal VAT. These results are also found in the literature …”
Section: Discussionmentioning
confidence: 74%